The Effect of Orlistat, Green Coffee Bean Extract, and Its Combinations on Lipid Profi le and Adiponectin Levels - Joko Setyono; Dwi Adi Nugroho; Mustofa Mustofa; Saryono Saryono (Jurnal Ners, 2014)
Introduction: Obesity prevalence is estimated increases, reached 19.1% of the population aged 15 years and over. This study aimed to determine the differences of the anti- obesity effect of orlistat, an extract of green coffee beans (Coffea canephora robusta), and its combination to the adiponectin levels and lipid profile.Method: This research was true experimental post -test only with control group design with completely randomized design (CRD). Experimental animals (Rattus novergicus) were divided into 6 group, group 1 ( negative control ), group 2 ( positive control ), group 3 was group of obese rats fed orlistat dose of 15.9 mg/kg, group 4 was the group of obese rats were fed ethanol extract of green coffee beans dose of 400 mg/kg, group 5 was the group of obese rats were given water extract of green coffee beans dose of 400 mg/kg, and group 6 was group of obese rats were fed a combination of orlistat dose of 15.9 mg/kg and ethanol extract of green coffee beans at a dose of 400 mg/kg. Lipid profi les and adiponectin levels were measured with a spectrophotometer at 500nm absorbance. The data were analyzed by one-way ANOVA, and then post hoc Least Significant Difference (LSD) with α = 0.05.Results: Ethanol extract of green coffee is more effi cient in lowering LDL cholesterol, increasing HDL cholesterol, and lowering the total cholesterol levels on HFD diet-induced mice, but there was no difference in lowering triglycerides . The combination of ethanol extract of green coffee with orlistat showedthe increasing of adiponectin levels were highest than the other treatment groups.Conclusion: The ethanol extract of green coffee readily diffuses through the digestive tract epithelium. Green coffee contains chlorogenic acid active compounds that can increase the body’s metabolism, increase fatty acid oxidation, reduce levels of triglycerides in the liver, and working to inhibit lipase and amylase pancreaticenzymes. In addition to chlorogenic acid, polyphenol content in coffee is also potentially reduce visceral fat accumulation. Preparations extract by ethanol allows the absorption process is done effi ciently and quickly.